Evidence based practice: knowledge, attitude and practice among undergraduate and postgraduate medical students of a medical college in North Karnataka, India - R., Manjula; Srivastava, Anjani Kumar; Dorle, Ashok S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Evidence based practice (EBP) is based on the integration of the best research evidence with clinical expertise to facilitate clinical decision making. Those patients who receive evidence-based therapies have better outcomes than those who do not.Evidence-based medicine is becoming a specialty in its own right, and it's an area that medical students should pay close attention to when determining their path. The objective of the study was to assess the knowledge, attitude and practice regarding evidence based practice among the undergraduate and postgraduate students of a medical college in North Karnataka. Methods: After obtaining ethical clearance from institutional ethical committee, this cross-sectional study was conducted in a Medical College in North Karnataka from November 2016–January 2017. All the interns and postgraduates studying in the College were included in the study. After obtaining informed consent, data was collected through pre-designed semi-structured questionnaire. Data was compiled and tabulated by using MS Excel and was analyzed. Results: Overall, majority of the participants hold positive attitudes toward EBP but lack sufficient knowledge and skills for implementation. The main barriers to implement EBP are insufficient time to read scientific research articles and the cost to its access. Conclusions: More focus should be given to EBP from the medical school itself, either through continuing medical education or various workshops, it can even be included in the curriculum so that all the undergraduate medical students can be sensitized to it from a very initial stage.